(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The construction industry is recognized to be highly prone to risks and is characterized to be very complex, dynamic, and unique where uncertainties arise from various sources. The main objective of this research was to identify the factors affecting occupational health risk during construction of high rise building to assess the risk during different construction activities. In the present study, field survey is done at forty two sites in western Maharashtra such as construction sites in Pune, Satara, sangli and Kolhapur city and data is collected for assessment of risk causes affecting occupational health in construction. In this study various risk causes were found out with help of questionnaire survey. These questionnaires were given to the experienced site engineers and data were collected. These data was then analyzed with the help of two different methods, named Relative Importance Index method and T-test analysis using SPSS. Results were calculated and shown with the help of graphical and tabular representation.